EVALUASI MUTU PELAYANAN FARMASI KLINIK PADA PUSKESMAS PATTALLASSANG DI KABUPATEN TAKALAR - Helmatiana Tandirogang; Ismail Ibrahim; Ida Adhayanti (Jurnal Buana Farma, 2023)
One of the government's efforts to realize health development for the community is to create a Community Health Center (Puskesmas). The Puskesmas is responsible for providing comprehensive, integrated and sustainable first-level health service activities. Pharmaceutical care (pharmaceutical care) has undergone a paradigm shift from initially only focusing on drug management (drug oriented) to developing into services that also aim to improve the quality of life of patients (patient oriented). Standard clinical pharmacy is very important to note because it is directly related to patients so that it can have an impact on reducing the length of patient care and reducing therapy costs. 74 of 2016. This research is a quantitative descriptive study using observational data and retrospective data at the Pattallassang Health Center in Takalar District. Based on the results of the study, it was found that the percentage of conformity of the quality of clinical pharmacy services at the Pattallassang Health Center, Takalar Regency, based on Permenkes Number 74 of 2016, was 38.88% in the unfavorable category. This is because there are 11 assessment indicators (prescription review, labeling, delivery accompanied by information, polypharmacy, counseling, drug information service documentation, visit documentation, MESO documentation, PTO documentation, drug costs per prescription visit, and number of items per prescription) that do not meet standards and for those that meet there are 7 indicators (time to prescribe, generic preparations, use of antibiotics in non-specific diarrhea, ORS and zinc for diarrhea, antibiotics in ARI, injections and patient satisfaction) out of 18 research indicators.